Marketing horti-tourism and rural development for leveraging tourism agenda 2030: a perspective article - Mohammed, Iddrisu; Mahmoud, Mahmoud Abdulai; Hinson, Robert Ebo (Tourism review (Association internationale d'experts scientifiques du tourisme), 2024)
Purpose This paper aims to draw the attention of the academic scholars to how marketing of horti-tourism can take action to contribute to tourism agenda 2030. Design/methodology/approach Reviewing literature on tourism, this paper builds a case for marketing horti-tourism based on the research gaps in literature, and future research directions are proposed to aid in the achievement of tourism agenda 2030. Findings Scholarly research on horti-tourism remains scarce, and more research attention is suggested on this subject matter. The tourism sector produced varied forms of tourism where horti-tourism is associated with horticulture farms, vegetable gardens and flower gardens which provide direct gains such as employment creation, foreign currency earnings, income generation source, poverty reduction and other gainful commercial activities. Despite the importance attached to this form of tourism in literature, less research has been conducted to market its relevance to nations and businesses. Much academic studies are needed to project this form of tourism. Originality/value This perspective paper serves as a call for tourism firms, governments and other stakeholders within and outside to make theoretical and practical contributions by marketing horti-tourism destinations to visitors which aid in the UN Tourism Agenda of 2030. 目的 这篇文章提出观点和视角, 旨在引起学术界学者对 2030 年旅游议程的关注, 通过园艺旅游营销, 如何采取行动为推动 2030 年旅游议程做出贡献。 设计/方法/途径 本文回顾了旅游业的相关文献, 根据文献中的研究空白构建了营销园艺旅游的案例, 并提出了未来的研究方向, 以帮助实现 2030 年旅游议程。 发现 关于园艺旅游的学术研究仍然很少, 建议对该主题进行更多的研究关注。旅游业产生了多种旅游形态, 其中园艺旅游与园艺农场、菜园和花园相关, 提供直接收益：如创造就业、外汇收入、拓展收入来源、减贫和其他有收益的商业活动。尽管在众多文献中都很重视这种旅游形态, 但很少研究其与国家和企业的相关性, 需要大量的学术研究来预测这种形式的旅游。 原创性/价值 这篇观点文章呼吁国内外的旅游公司、政府和其他利益相关者通过向游客营销园艺旅游目的地来进一步取得理论和实践成果, 以帮助推动联合国 2030 年旅游议程。 Objetivo Este documento tiene como meta analizar cómo el marketing de Horti-turismo puede contribuir al desarrollo de la agenda del turismo 2030. Diseño/metodología/enfoque Se ha realizado una revisión de la literatura en bases de datos científicas de impacto a nivel internacional sobre la comercialización del horti-turismo. Los Hallazgos La investigación prospectiva sobre horti-turismo sigue siendo escasa y se sugiere más atención científica sobre este tema. El sector turístico produjo variadas formas de turismo donde el horti-turismo está asociado con granjas de horticultura, jardines vegetales y jardines de flores que proporcionan beneficios directos como la creación de empleo, ganancias en divisas extranjeras, fuente de generación de ingresos, reducción de la pobreza y otras actividades comerciales lucrativas. A pesar de la importancia atribuida a esta forma de turismo en la literatura, se ha prestado menos atención en la comercialización a las naciones y las empresas. Se ha puesto de manifiesto la necesidad de desarrollar más estudios para formentar esta forma de turismo. Originalidad/valor Este artículo exploratorio permite a las empresas de turismo, los gobiernos y otras partes interesadas dentro y fuera realizar contribuciones teóricas y prácticas a fin de comercializar sus productos en destinos de horti-turismo y, con ello, fomentar el desarrollo Agenda de Turismo de las Naciones Unidas de 2030.